Delayed presentation of surgically induced scleral necrosis after I-BRITE procedure treated with immunosuppressive therapy - Azar, Nadim S.; Ruiz-Lozano, Raul E.; Quiroga-Garza, Manuel E.; Soifer, Matias; Mousa, Hazem M.; Komai, Seitaro; Leverenz, David L.; Perez, Victor L. (Digital Journal of Ophthalmology, 2023)
Surgically induced scleral necrosis (SISN) is an uncommon complication of ocular procedures. Cosmetic eye-whitening surgery involves conjunctival and Tenon’s capsule dissection, cautery, and mitomycin C application. We report the case of a 36-year-old white woman referred to our clinic for severe pain, scleral inflammation, and necrosis in both eyes 9 years after I-BRITE, an elective eye-whitening procedure. An extensive workup yielded negative results. The patient improved with aggressive lubrication and topical and high-dose systemic prednisone (60 mg), with recurrence upon steroid tapering. Concomitant weekly methotrexate was added, resulting in inflammatory control and allowing discontinuance of topical and oral steroids.